2021
DOI: 10.1016/j.jcomdis.2020.106070
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility, usability and acceptability of a tablet-based aphasia therapy in the acute phase following stroke

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Another factor that could affect the technical feasibility of self-managed computer-based aphasia treatment was the ability of participants to use the SPT independently: five of the six participants (83%) achieved independent use of the SPT. This is similar to the percentage reported in other studies of self-delivered, computer-based treatments (e.g., Kurland et al 2018;De Cock et al, 2021). The level of independent use likely reflects the aphasia-friendly design of the human-computer-interface (HCI) of the SPT which was informed by the small but developing field of research into aphasiafriendly HCIs (e.g., Brandenburg et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Another factor that could affect the technical feasibility of self-managed computer-based aphasia treatment was the ability of participants to use the SPT independently: five of the six participants (83%) achieved independent use of the SPT. This is similar to the percentage reported in other studies of self-delivered, computer-based treatments (e.g., Kurland et al 2018;De Cock et al, 2021). The level of independent use likely reflects the aphasia-friendly design of the human-computer-interface (HCI) of the SPT which was informed by the small but developing field of research into aphasiafriendly HCIs (e.g., Brandenburg et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…The main premise in pursuing technology-assisted therapy is to facilitate access (by reducing costs and/or logistical barriers like location/ transportation) and/or increase the amount of practice an individual can complete, given the large number of hours needed to facilitate learning. Good compliance, ease-of-use, and satisfaction have been reported with these studies [101,102,103], which is encouraging given a primary motivation of increasing total amount of practice time. Results from VR, telerehabilitation, and computer-/tablet-based treatment studies are overwhelmingly positive, but lack of comparison studies and/or adequate control groups/tasks makes it difficult to identify superior protocols or attribute outcomes to the technological component of the treatment [104,105].…”
Section: Language Speech and Communicationsupporting
confidence: 61%
“…However, in all the above studies, only participants with mild stroke and the ability to walk were included. Only 1 of the included studies, Kizoni et al (46), targeted the assessment of upper limb deficits through app solutions supporting hand activity among stroke survivors. One of the included studies showed that an app solution was reliable to support the measurement of pulmonary function among chronic stroke survivors (71).…”
Section: App Solutions To Support Assessment (N = 16)mentioning
confidence: 99%